2012
DOI: 10.1037/a0026208
|View full text |Cite
|
Sign up to set email alerts
|

Perceived racism and mental health among Black American adults: A meta-analytic review.

Abstract: The literature indicates that perceived racism tends to be associated with adverse psychological and physiological outcomes; however, findings in this area are not yet conclusive. In this meta-analysis, we systematically reviewed 66 studies (total sample size of 18,140 across studies), published between January 1996 and April 2011, on the associations between racism and mental health among Black Americans. Using a random-effects model, we found a positive association between perceived racism and psychological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

31
464
3
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 553 publications
(503 citation statements)
references
References 94 publications
31
464
3
5
Order By: Relevance
“…Kwate and Goodman (2015) call attention to methodological difficulty in proving the association between exposure to racism and the development of mental disorders with longitudinal section studies, which makes these studies expensive. However, the experience of racism has proven association with feelings of loneliness among young people (Priest et al, 2014), days of poor mental health (Kwate;Goodman, 2015) and symptoms of anxiety and depression (Pieterse et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Kwate and Goodman (2015) call attention to methodological difficulty in proving the association between exposure to racism and the development of mental disorders with longitudinal section studies, which makes these studies expensive. However, the experience of racism has proven association with feelings of loneliness among young people (Priest et al, 2014), days of poor mental health (Kwate;Goodman, 2015) and symptoms of anxiety and depression (Pieterse et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Discrimination is profoundly stressful both psychologically and physiologically (Mays et al, 2007;Pascoe & Smart Richman, 2009;Pieterse et al, 2012), and racial discrimination has been found to have a more deleterious impact on alcohol use among African Americans who endorse drinking as a coping strategy versus African Americans who do not . Moreover, evidence suggests that drinking to cope may paradoxically increase negative mood as well as deplete self-regulatory resources (Armeli et al, 2014), a process that could trigger a maladaptive cycle in which coping skills are further deteriorated and alcohol use becomes a more primary means of coping.…”
mentioning
confidence: 99%
“…DuBois in 1898 and Franz Fanon in the 1960s have suggested that the experience of racism exacts a "significant psychological toll on people" (p. 2). Furthermore, scholars have been considering the impact of racism on the mental health of students for a very long time (see Pieterse, Todd, Neville, & Carter, 2012;Harvey, 1984). As Harvey (1984) reminds us, no "other social institution impacts on the mental health of so many Black people in such a direct and significant way as does the educational system" (p. 444).…”
Section: The Context Of Racism In Schoolsmentioning
confidence: 99%
“…A recent meta-analysis of 66 studies between 1996 and 2011 demonstrate the real and significant link between the perception of racism and mental health (Pieterse, et al, 2012). There is discussion in the field of psychology about how to diagnose and treat both racism and patient responses to racism.…”
Section: Racism and Mental Healthmentioning
confidence: 99%